Severe injuries in football players. Influencing factors - Chomiak, J.; Junge, A.; Peterson, L.; Dvorak, J. (The American Journal of Sports Medicine, 2000)
The aims of this prospective study were to analyze factors related to the occurrence of severe football injuries in players of different ages (14 to 42 years) and different skill levels (local teams to first league teams). In the Czech Republic, 398 players were followed up for 1 year, during which time they sustained 686 injuries. Of these, 113 (16.5%) were severe injuries. Ninety-seven severe injuries (86%) were able to be documented in detail. Trauma was the cause of 81.5% of the injuries and overuse was the cause of 18.5%. Joint sprains predominated (30%), followed by fractures (16%), muscle strains (15%), ligament ruptures (12%), meniscal tears and contusions (8%), and other injuries. Injuries to the knee were most prevalent (29%), followed by injuries to the ankle (19%) and spine (9%). More injuries occurred during games (59%) than in practice. Twenty-four percent of the injured players had suffered a previous injury of the same body part. Forty-six percent of injuries were caused by contact and 54% involved no body contact. Thirty-one percent of severe injuries were caused by foul play. From these results and the analysis of injuries in specific body parts, the following factors were determined to influence the occurrence of severe injuries: 1) personal factors (intrinsic): age of player, previous injuries, joint instability, abnormality of the spine, poor physical condition, poor football skills, or inadequate treatment and rehabilitation f injuries; 2) environmental factors (extrinsic): subjective exercise overload during practices and games, amount and quality of training, playing field conditions, equipment (wearing of shin guards and taping) and violations of existing rules (foul play).